Leveraging ChatGPT and artificial intelligence for effective customer engagement - Bansal, Rohit; Ngah, Abdul Hafaz; Chakir, Aziza; Pruthi, Nishita (Hershey, PA : Business Science Reference, 2024)
'This book provides deeper understanding on the role of Artificial Intelligence powered ChatGPT in enhancing better customer engagement and gain competitive edge'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: ChatGPT; Customer relations; Marketing -- Technological innovations; Artificial intelligence